Outcome of minimally invasive plate osteosynthesis in distal tibial fractures (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Distal tibial fractures present as a major challenge for the orthopedic trauma surgeons. Most non-operative treatments result in non-union or malunion and needs prolonged immobilization of the knee and ankle joints, with resulting stiffness. Open reduction and internal fixation as well as external fixation has high rate of infection and non-union. Minimally Invasive Plate Osteosynthesis has been shown to have a better outcome and has been the procedure of choice in most distal tibial fractures since the introduction of the locking compression plate. The objective of the study is to review the outcome of Minimally Invasive Percutaneous Osteosynthesis (MIPO) in unstable distal tibial fractures.Methods: Charts of patients who underwent MIPO from the year 2008 to 2013 for unstable distal tibial fractures over five years at Patan Hospital and Om Hospital were reviewed. All displaced closed fractures and Gustillo Anderson Type I and II fractures were included in the study. Plates consisted of the anatomically contoured 4.5 mm LCP and 3.5 mm LCP-Pilon form plate. A simple uniplanar external fixator was used to retain the reduction till the plate was inserted and secured with locking screws. The outcome of MIPO in distal tibial fractures were followed up and evaluated.  Clinical and radiological assessments were performed at 6 weeks, and at 3, 6, 9, 12 and 24 months.Results: Of the 75 patients (45 male, 30 female) age ranging from 19 to 70 years (mean 47 years), 5 patients were lost to follow-up. 28 patients at 3 months, 32 at 6 months, and 8 at 9 months met the criteria for a healed fracture. Two patients required autologous bone grafting at 9 months for non-union ultimately resulting in the fracture union at 16 months. There was one malunion attributable to the loss of reduction during plate fixation. There were no deep infections, no soft tissue complications and no failures of fixation. The cause of fracture were RTA (n=35), fall from height (n=9), twisting of ankle as a result of fall from standing height (n=22), and others (n=11). The mean time for surgery from the time of injury was 5 (range, 2 to 14) days; the mean hospital stay was 10 (range, 7 to 21) days.Conclusion: MIPO is an effective treatment for closed, unstable fractures of the distal tibia, avoiding the complications associated with more traditional methods of internal fixation and/or external fixation.Journal of Society of Surgeons of NepalVol. 17, No. 2, 2014, Page: 7-11